Characterization of four polymorphic genes controlling red leaf colour in lettuce that have undergone disruptive selection since domestication. Issue 2 (8th August 2019) - Su, Wenqing; Tao, Rong; Liu, Wenye; Yu, Changchun; Yue, Zhen; He, Shuping; Lavelle, Dean; Zhang, Weiyi; Zhang, Lei; An, Guanghui; Zhang, Yu; Hu, Qun; et al.
Summary: Anthocyanins protect plants from biotic and abiotic stressors and provide great health benefits to consumers. In this study, we cloned four genes ( Red Lettuce Leaves 1 to 4: RLL1 to RLL4 ) that contribute to colour variations in lettuce. The RLL1 gene encodes a bHLH transcription factor, and a 5‐bp deletion in some cultivars abolishes its function to activate the anthocyanin biosynthesis pathway. The RLL2 gene encodes an R2R3‐MYB transcription factor, which was derived from a duplication followed by mutations in its promoter region. The RLL3 gene encodes an R2‐MYB transcription factor, which down‐regulates anthocyanin biosynthesis through competing with RLL2 for interaction with RLL1; a mis‐sense mutation compromises the capacity of RLL3 to bind RLL1. The RLL4 gene encodes a WD‐40 transcription factor, homologous to the RUP genes suppressing the UV‐B signal transduction pathway in Arabidopsis; a mis‐sense mutation in rll4 attenuates its suppressing function, leading to a high concentration of anthocyanins. Sequence analysis of the RLL1 ‐ RLL4 genes from wild and cultivated lettuce showed that their function‐changing mutations occurred after domestication. The mutations in rll1 disrupt anthocyanin biosynthesis, while the mutations in RLL2, rll3 and rll4 activate anthocyanin biosynthesis, showing disruptive selection for leaf colour during domestication of lettuce. The characterization of multiple polymorphic genes in this study provides the necessary molecular resources for the rational breeding of lettuce cultivars with distinct levels of red pigments and green cultivars with high levels of health‐promoting flavonoids.